2010
DOI: 10.1029/2009jg001077
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary geochemical composition and flux of aeolian dust to the San Juan Mountains, Colorado, United States

Abstract: , with individual deposition events reaching as high as 2 g m −2 . Dust deposited in the San Juan Mountains was primarily composed of silt-and clay-sized particles, indicating a regional source area. The concentrations of most major and minor elements in this dust were similar to or less than average upper continental crustal concentrations, whereas trace element concentrations were often enriched. In particular, dust collected from the San Juan Mountain snowpack was characterized by enrichments of heavy metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(143 citation statements)
references
References 96 publications
11
128
1
Order By: Relevance
“…Precipitation has been shown to be an important C input for carbon-poor environments, such as coastal areas (Kieber et al, 2006(Kieber et al, , 2007 and the open ocean (Willey et al, 2000, Economu and Mihalopoulos, 2002, Jurado et al, 2008. For alpine environments, Litaor (1987) and Ley et al (2004) in the Colorado Rocky Mountains and more recently Mladenov et al (2009Mladenov et al ( , 2010 in the Sierra Nevada of Spain reported that aeolian deposition comprised about 10 % to 20 % organic C. Lawrence et al (2010) also found surprisingly high organic C content in dust deposition. Mladenov et al (2009) used spectroscopic techniques (UV-vis absorbance and fluorescence) in combination with air mass backward trajectories to demonstrate that water soluble organic carbon (WSOC) from dust emitted in Africa and deposited at an alpine site in Spain contained substantial amounts of humic-like fluorescent compounds.…”
Section: N Mladenov Et Al: Atmospheric Deposition As a Source Of Camentioning
confidence: 91%
See 2 more Smart Citations
“…Precipitation has been shown to be an important C input for carbon-poor environments, such as coastal areas (Kieber et al, 2006(Kieber et al, , 2007 and the open ocean (Willey et al, 2000, Economu and Mihalopoulos, 2002, Jurado et al, 2008. For alpine environments, Litaor (1987) and Ley et al (2004) in the Colorado Rocky Mountains and more recently Mladenov et al (2009Mladenov et al ( , 2010 in the Sierra Nevada of Spain reported that aeolian deposition comprised about 10 % to 20 % organic C. Lawrence et al (2010) also found surprisingly high organic C content in dust deposition. Mladenov et al (2009) used spectroscopic techniques (UV-vis absorbance and fluorescence) in combination with air mass backward trajectories to demonstrate that water soluble organic carbon (WSOC) from dust emitted in Africa and deposited at an alpine site in Spain contained substantial amounts of humic-like fluorescent compounds.…”
Section: N Mladenov Et Al: Atmospheric Deposition As a Source Of Camentioning
confidence: 91%
“…High Ca 2+ and DOP content is characteristic of dust deposition to the Colorado Rocky Mountains from the Colorado Plateau and Mojave Desert (Lawrence et al, 2010), which is most pronounced during the spring. Three high Ca 2+ precipitation events measured in 2010 (4, 11, and 18 May) had backward trajectories showing a Colorado Plateau air mass source (Supplement Fig.…”
Section: Seasonality and Sources Of Atmospheric Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sustained level of increased dust production and deposition appears to have been increasing further over recent decades (Brahney et al, 2013), and recent hydrologic studies show it has been affecting snowmelt rates and runoff timing and volume from the Colorado River Basin Skiles et al, 2012). Though some global dust sources exceed the intensity of dust emission in the southwestern US (e.g., Yu et al, 2012), multiple lines of evidence, including backtrajectory analysis, dust particle sizes, and synoptic event drivers, demonstrate the primarily regional provenance of dust deposited on UCRB snowpacks Neff et al, 2008;Lawrence and Neff, 2009;Lawrence et al, 2010;Steenburgh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Dust contributes substantial loading of soluble salts, metals, and metalloids to snowpack (Turk et al, 2001;Clow et al, 2002;Ingersoll et al, 2008;Lawrence et al, 2010;Rhoades et al, 2010;Carling et al, 2012). Trace metal concentrations in dust (e.g., As, Cd, Cu, Mo, Pb, and Zn) are enriched relative to average upper continental crust, and dust-derived trace metals are more available and mobile relative to other sources (Lawrence and Neff, 2009;Lawrence et al, 2010Lawrence et al, , 2013. Dust sources impacting the Teton Range include the Snake River Plain agricultural area to the west and oil and gas extraction to the south and east (Spaulding et al, 2015).…”
Section: Trace Element Contributions From Atmospheric Deposition and mentioning
confidence: 99%